Oral health knowledge, practice, oral hygiene status, and dental caries prevalence among visually impaired children in Bangalore - S T Prashanth; Sudhanshu Bhatnagar; Usha Mohan Das; H Gopu (Wolters Kluwer Medknow Publications, 2011)
Introduction: Visually impaired children daily face challenges for bearing their everyday skills. Maintenance of proper oral hygiene is one among them. Aim: The aim of the study was to assess the oral health knowledge, practice, oral hygiene status, and dental caries prevalence among visually impaired children in Bangalore. Materials and Methods: A total of 85 children were asked verbally a questionnaire regarding the frequency of brushing, cleaning tools, use of dentifrice, knowledge about the role of sugar in producing dental decay, and frequency of visit to the dentist. All children were screened and DMF and def scores were recorded and oral hygiene status were assessed by Green and Vermillion index. Results: Green and Vermillion index. Kruskal Wallis Chi square test was performed and no statistically significant results were obtained with DMF and def scores as well as OHI scores across different ages in the range of 8 to 13 years. A highly statistically significant result was obtained with dental caries prevalence and oral hygiene status of visually impaired children. Conclusions: The present study shows not much worsening of oral health status in the study population. A little extra care by the parent or caretaker regarding oral hygiene can give drastic results in reduction of dental caries.